Students’ Perceptions on the Effectiveness of YouTube in Improving Their English-Speaking Skill in English Education Students - Sorga, Debora Nadya Rapita; Zuraida, Zuraida (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to investigate students’ perceptions of YouTube as a learning tool for enhancing their speaking ability. This research employed a descriptive quantitative method with a survey design. Data were collected from 127 students of the English Education Study Program at Sriwijaya University using a Likert-scale questionnaire distributed both online and offline. The validity and reliability of the instrument were tested through expert judgment and statistical analysis, resulting in a Cronbach’s Alpha score of 0.766, indicating good reliability. The data were analyzed using descriptive statistics through SPSS to identify trends in students’ perceptions. The findings revealed that most students strongly agreed that YouTube supports improvements in pronunciation, fluency, vocabulary enrichment, intonation, and natural expression. Furthermore, students perceived YouTube as enjoyable, motivating, flexible, and easily accessible for independent practice beyond the classroom. These results demonstrate that YouTube plays a significant role in fostering confidence, engagement, and continuous improvement in English-speaking skills. In conclusion, YouTube is perceived as an effective and valuable supplementary tool for learning English speaking, providing both accessibility and flexibility. The study suggests that integrating YouTube into formal language instruction can enhance student motivation and support more effective speaking practice.